Antero-lateral ST-segment elevation myocardial infarction in a patient with stent in the left anterior descending implanted ten years earlier and angiographic control two weeks earlier - Filipska, Anna; Dąbrowski, Marek; Frankowski, Bartosz; Zbyszyński, Bogdan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
The article refers to a case of a woman who underwent an anterior wall ST-segment elevation myocardial infarction (STEMI) and angioplasty left anterior descending (LAD) 10 years ago. The angiography that she underwent 2 weeks before the next STEMI did not show any relevant atherosclerotic changes. Nonetheless, she was hospitalized 14 days later due to a new ST elevation in a scar after pre-existing myocardial infarction. After a coronarography we identified an occlusion LAD below the stent. In this publication we discuss the problem of the lack of a simple, cheap and unmistakable method that would enable us to identify an unstable sclerotic plaque.